Variation in physicochemical and biochemical soil properties among different plant species treatments early in the restoration of a desertified alpine meadow. (23rd July 2019) - Liu, Lin; Zeng, Kai; Wu, Ning; Zhang, Xinquan; Sun, Feida; Chen, Dongming; Gao, Wuchao; Zhou, Jiqiong; Zhao, Jingxue; You, Chengming; Sun, Geng
Abstract: Soil nutrients, enzyme activities, and microbial biomass have important significance for biogeochemical cycles and are affected by vegetation restoration in degradation ecosystems. To explore the effects of replanting different plant species on soil restoration in a desertified alpine meadow on the eastern Tibetan Plateau and to optimize the restoration process with locally appropriate plant species, the soil physicochemical and biochemical properties were measured beneath the plant species Rhodiola kirilowii, Salix cupularis, and Kengyilia rigidula over two periods of vegetative growth (2 years and 5 years). The results showed that all the soil properties significantly improved over the recovery periods ( p  < .001) and the plant species significantly affected the patterns of soil bulk density, available resources, and biochemical properties ( p  < .05). However, R .  kirilowii improved soil properties most significantly among the three plant species as the recovery time elapsed, and these improvements were strongly related to the greatest fresh vegetation biomass and coverage. Furthermore, R .  kirilowii enhanced microbial biomass phosphorus even more, which is an important available phosphorus stock in the soil, and more effectively promoted the development of soil fungi than the two other species. Therefore, we suggest that R .  kirilowii is the preferred species of the three to expedite the recovery of desertified alpine soil, and that the appropriate addition of P fertilizer and propelling the development of specific fungi groups in the soil are key to soil restoration in the desertified alpine meadow.